2019
DOI: 10.3390/su11154193
|View full text |Cite
|
Sign up to set email alerts
|

Is Smart Housing a Good Deal? An Answer Based on Monte Carlo Net Present Value Analysis

Abstract: The smart cities are considered to be an engine of economic and social growth. Most countries started to convert their existing cities into smart cities or construct new smart cities in order to improve the quality of life of their inhabitants. However, the problem that facing those countries while applying the concept of smart cities is the costs, especially for the residential sector. Despite the high initial and even operation costs for adopting different technologies in smart housing; the benefits could ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In [31] the influence of smart grids on the electrical distribution networks is analyzed, highlighting the differences in implementing smart meters in developed and developing states. [32] demonstrates the cost of executing smart housing technology, and regardless of the initial greater costs, the advantages could potentially compensate expenses in the lifespan of the project. Using NPV (Net Present Value) of the smart economic house model, this study found positive NPVs for all meters, demonstrating the feasibility of the solution.…”
Section: B Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In [31] the influence of smart grids on the electrical distribution networks is analyzed, highlighting the differences in implementing smart meters in developed and developing states. [32] demonstrates the cost of executing smart housing technology, and regardless of the initial greater costs, the advantages could potentially compensate expenses in the lifespan of the project. Using NPV (Net Present Value) of the smart economic house model, this study found positive NPVs for all meters, demonstrating the feasibility of the solution.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…To ensure the feasibility study's reliability, it is crucial to analyze the time value of money. To assess the project's individual profitability, the NPV calculation is employed, which involves estimating future cash flows over a specified time frame [32].…”
Section: A) Net Present Valuementioning
confidence: 99%
“…The economic viability and feasibility of using smart technologies in buildings are an issue discussed by many studies. Despite the high initial cost of smart technologies compared to the conventional ones, the benefits could exceed those costs within the lifespan of the project [12]. The initial cost, energy savings, and payback period of smart buildings technologies vary widely across technology and building types.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter aspect, however, there are some differences in the approaches to the conceptualisation of smart housing. In particular, according to Elariane and Dubé [14] the above concept consists of five dimensions: smart meters; sensors or monitoring systems; automatic control system; user interface; and communication network to connect the devices with each other. This standpoint highlights the use of technology to improve both the quality of life of the household members and energy efficiency [15].…”
Section: Introductionmentioning
confidence: 99%